Baton twirling: another cause of eye injury. Issue 12 (December 1987) - Fern, A I; Kyle, P; Allan, D
Abstract : Baton twirling is an increasingly popular sport, with an estimated 5000 participants in Scotland alone. The baton, weighing over 200 g, is spun at high speeds and frequently thrown over 40 feet (12 m) into the air. We report a case of a 17-year-old girl who sustained a serious eye injury after being struck by a baton. The occurrence of eye injury has not been reported in this sport, and we discuss the potential for injury.